Fungal infection profile in burn patients at a tertiary care centre of India - Ahmad, Imran; Khurram, Mohammed Fahud; Maurya, Sudheer Kumar; Maurya, Rajesh Kumar; Sheikh, Mohd. Tafazul (International Journal of Research in Medical Sciences, 2018)
Background: Burn patients are at high risk of infections and burn wound infection is one of the most important factor responsible for their morbidity and mortality. Burn patients have increased incidence of fungal infection in comparison to others. Fungal infection is difficult to diagnose because it has similar symptoms like bacterial infections. Common fungal organism causing burn wounds infections are Candida sp., Aspergillus sp., non albicans Candida, Zygomycetes etc. Methods: This prospective study was carried out in Department of Burn, Plastic and Reconstructive Surgery, J.N.M.C.H., Aligarh Muslim University, India from December 2015 to June 2017. Patients having 20 to 60% body surface area involvement with more than 5 years of age with no comorbidity were included in this study. Results: In our study, total 126 patients were included, 9 male patients (18.37%) were found fungal culture positive whereas 14 females (18.18%) were culture positive. 12 patients (9.52%) were found to be positive for Candida albicans, 6 patients (4.76%) were Aspergillus flavus positive, 3 patients (2.38%) were positive for Non Candida albicans and 2 patients (1.59%) were positive for Aspergillus niger. Conclusions: Fungal burn wound infections are one of the most common cause of late onset morbidity and mortality in burn patients. So, high level of suspicion and tissue culture are essential in making early diagnosis and treatment. Judicious use of antibiotics are also necessary for decreasing its incidence.